Characterization of Two Historical Postage Stamps Made from Cotton Fibers and Their Restoration Trials Based on the Experimental Studies - Maisa M.A. Mansour; Yassin E. Zidan; Abou El Fettouh A Abd El Hakim; Mohamed Mahmoud Allam; Hayssam M. Ali; Mohammad Akrami; Mohamed Z. M. Salem (Journal of Chemistry)
Ancient stamps are suffering from the destructive effects of different kinds of inks that were prepared from different ingredients. Two Egyptian historical postage stamps printed in blue and red printing inks were evaluated and examined for their composition using a light microscope, SEM-EDS, FTIR, and Raman spectroscopic analyses. Mechanical, chemical, and deacidification treatments were done for the two stamps. Model stamps were made from the cotton pulp in the book house to simulate historical stamp paper with an average thickness of 11 microns. The unprinted and printed paper samples with printing inks that aged and unaged were treated with 0.7% Klucel G, 0.2% TiO2 NP, or a mixture of 0.7% Klucel G + 0.2% TiO2 NP, and the color change was measured and compared with the blank samples. The two stamps are suffering from high pH, where the margin color of the stamps changed to yellow-brown with weakness of the stamp paper. By SEM examination, stamps have suffered from fibers’ weakness and dryness resulting from the self-oxidation reactions. EDS elemental composition of the red stamp showed the presence of C, O, Na, Al, Si, Mg, S, Ca, Ba, and Fe, while in the blue stamp, it was C, O, Na, Al, Si, P, S, Cl, and Ca. Raman spectrometer wavelengths turn out that the blueprinting ink of the stamp was characterized with spectra of ultramarine blue (lazurite), while hematite was characterized by the red stamp. FTIR analysis for the printing inks identified that gum Arabic sample and linseed oil were the binding and color medium, respectively. From the model trials, it was observed that the treatment of a mixture of Klucel G and TiO2 NP had the best properties for the consolidation of stamps. The two historical stamps were documented through different spectroscopic analyses, and from the restoration trials, it was observed that the mixture of 7% Klucel G + 0.2% TiO2 NP appeared to be a new and effective method for recovering the historical postage stamps.